2002
DOI: 10.1046/j.1464-5491.2002.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐beta 1, 2, 3 and receptor type I and II in diabetic foot ulcers

Abstract: The lack of TGF-beta1 up-regulation in both diabetic foot ulcers and venous ulcers may explain the impaired healing in these chronic wounds, and could represent a general pattern for chronicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
128
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(136 citation statements)
references
References 26 publications
5
128
0
3
Order By: Relevance
“…Diabetes may influence foot wound healing in many ways, including an impairment of peripheral circulation, altered leucocyte function, disturbed balance of cytokines and proteases, and even chronic hyperglycaemia itself [78,79,80]. However, until recently, the role of offloading in impaired wound healing has not been considered [81].…”
Section: Wound Healing and The Importance Of Offloadingmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes may influence foot wound healing in many ways, including an impairment of peripheral circulation, altered leucocyte function, disturbed balance of cytokines and proteases, and even chronic hyperglycaemia itself [78,79,80]. However, until recently, the role of offloading in impaired wound healing has not been considered [81].…”
Section: Wound Healing and The Importance Of Offloadingmentioning
confidence: 99%
“…Recent studies have also demonstrated other abnormalities frequently seen in chronic neuropathic diabetic foot ulcers. Jude et al described the lack of up-regulation of TGF-β1 in foot ulcers, and Lobmann and colleagues described increases in matrix metalloproteinases and decreased concentration of their inhibitors, both of which could explain impaired wound healing [79,80]. A lack of insulin-like growth factor-1 in the basal keratinocyte layer of biopsies from foot ulcers [93], and increased nitric oxide synthase activity in foot ulcers [94] may also be contributory to retarded wound healing in diabetes.…”
Section: Wound Healing and The Importance Of Offloadingmentioning
confidence: 99%
“…In 95% of children with atopic dermatitis, specific TGFb1 gene polymorphism coexisted with decreased TGFb1 production [91]. In patients with diabetic foot and leg ulcers due to chronic venous insufficiency, locally reduced levels of TGFb1 and its receptors have been shown [92]. In patients with resistant-to-treatment leg ulcers, a reduced TGFbRII expression in fibroblasts has been demonstrated [93].…”
Section: Tgfb1 In Pathologymentioning
confidence: 99%
“…Moreover, abnormalities in growth factor expression [45] and other aspects of cell biology have been defined in chronic wounds in diabetes, including changes in the relative concentrations of matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) [46]. Neutrophils and macrophages are also known to have impaired function in hyperglycaemia and this could have an adverse impact on healing [47,48].…”
Section: Compressionmentioning
confidence: 99%